1
$\begingroup$

Fix $m$ and $k$ natural numbers. Let $A_{m,k}$ be the set of all partitions divisions of $m$ into $k$ parts. That is:

$$A_{m,k} = \left\{ (n_1,\ldots,n_k) : n_i >0, \sum_{i=1}^k n_i = m \right\} $$

We are interested in the following sum $s_{m,k}$:

$$s_{m,k} = \sum_{ (n_1,\ldots,n_k) \in A_{m,k} } \prod_{i=1}^k \frac{1}{n_i} $$

Can you find $s_{m,k}$ explicitly, or perhaps its generating function or exponential generating function?

EDIT: Since order matters in the $(n_1,\ldots,n_k)$ this is not exactly a partition.

$\endgroup$
  • $\begingroup$ These sums satisfy the recurrence relation $$s_{m,k}=\sum_{n_k=1}^{m-k+1}\frac{s_{m-n_k,k-1}}{n_k}\;.$$ $\endgroup$ – joriki Feb 22 '13 at 21:29
2
$\begingroup$

I am not sure I understand the problem correctly, but $$ g(z) = \left( \frac{z}{1} + \frac{z^2}{2} +\frac{z^3}{3} + \ldots + \frac{z^q}{q} + \ldots \right)^k = \left( \log \frac{1}{1-z} \right)^k $$ looks like a good candidate to me, so that $$ s_{m,k} = [z^m] \left( \log \frac{1}{1-z} \right)^k.$$ This is the exponential generating function for a sequence of $k$ cycles containing a total of $m$ nodes, $$\mathfrak{C}(\mathcal{Z}) \times \mathfrak{C(\mathcal{Z})} \times \mathfrak{C(\mathcal{Z})} \times \cdots \times \mathfrak{C(\mathcal{Z})} = \mathfrak{C}^k(\mathcal{Z}) ,$$ so that $m! [z^m] g(z)$ gives the number of such sequences.

Since the components are at most $m$ we could truncate the inner logarithmic term at $z^m/m$, but I suspect the logarithmic form is more useful for asymptotics.

$\endgroup$
1
$\begingroup$

In fact the expansion coefficients of g(z) above provide the answer, and they have quite a simple closed-form expression. Changing k to q (just to allow and use k and j as a summation indices) we have in fact:

$$ \eqalign{ & \ln \left( {{1 \over {1 - x}}} \right)^{\,q} \quad \left| {\;0 \le {\rm integer}\,{\rm }q} \right.\quad = \left( {\sum\limits_{1\, \le \,k_{\,1} } {{{x^{\,k_{\,1} } } \over {k_{\,1} }}} } \right)\left( {\sum\limits_{1\, \le \,k_{\,2} } {{{x^{\,k_{\,2} } } \over {k_{\,2} }}} } \right) \cdots \left( {\sum\limits_{1\, \le \,k_{\,q} } {{{x^{\,k_{\,q} } } \over {k_{\,q} }}} } \right) = \cr & = \sum\limits_{0\, \le \,j} {\left( {\sum\limits_{\scriptstyle 1\, \le \,k_{\,i} \atop \scriptstyle \,k_{\,1} \, + \,k_{\,2} \, + \, \cdots \, + \,k_{\,q} \, = \,j} {{1 \over {k_{\,1} k_{\,2} \cdots k_{\,q} }}} } \right)x^{\,j} } = \cr & = \sum\limits_{0\, \le \,j} {{{q!} \over {j!}}\left[ \matrix{ j \cr q \cr} \right]\,x^{\,j} } = x^{\,q} \sum\limits_{0\, \le \,j} {{{q!} \over {\left( {q + j} \right)!}}\left[ \matrix{ q + j \cr q \cr} \right]\,x^{\,j} } \cr} $$

where ${\left[ \matrix{ j \cr q \cr} \right]}$ indicates the (unsigned) Stirling Number of 1st kind.

The above deriving from the double expansion : $$ {1 \over {\left( {1 - x} \right)^{\,y} }} = \left\{ \matrix{ = \sum\limits_{0\, \le \,j} {\,\left( { - 1} \right)^{\,j} \left( \matrix{ - y \cr j \cr} \right)x^{\,j} } = \sum\limits_{0\, \le \,j} {{{\left( { - 1} \right)^{\,j} } \over {j!}}\,x^{\,j} \left( { - y} \right)^{\,\underline {\,j} } } = \sum\limits_{\scriptstyle 0\, \le \,k \atop \scriptstyle 0\, \le \,j} {{1 \over {j!}}\left[ \matrix{ j \cr k \cr} \right]\,x^{\,j} y^{\,k} } \hfill \cr = \exp \left( {y\ln \left( {{1 \over {1 - x}}} \right)} \right) = \sum\limits_{0\, \le \,k} {{{y^{\,k} } \over {k!}}\left( {\ln \left( {{1 \over {1 - x}}} \right)} \right)^{\,k} } \hfill \cr} \right. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.